2018
DOI: 10.1007/s00394-018-1864-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol inhibits cancer stem cells and the metastatic capacity of triple-negative breast cancer cell lines by the simultaneous targeting of epithelial-to-mesenchymal transition, Wnt/β-catenin and TGFβ signaling pathways

Abstract: Purpose This study was aimed to determine the impact of hydroxytyrosol (HT), a minor compound found in olive oil, on breast cancer stem cells (BCSCs) and the migration capacity of triple-negative breast cancer (TNBC) cell lines through the alteration of epithelial-tomesenchymal transition (EMT) and embryonic signaling pathways. MethodsBCSCs self-renewal was determined by the mammosphere-forming efficiency in SUM159PT, BT549, MDA-MB-231 and Hs578T TNBC cell lines. Flow cytometric analysis of CD44 + /CD24 -/low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…Previous studies had highlighted an anti-tumorigenic potential of hydroxytyrosol due to its capacity to protect against oxidative DNA damage in non-malignant MCF10A breast cells ( 113 ). More recently, hydroxytyrosol was shown to have inhibitory effects on breast cancer stem cell (BCSC) self-renewal in a comprehensive investigation using multiple TNBC cell lines ( 57 ). Tumor enrichment of BCSC has been suggested to play a role in the aggressiveness and poor prognosis associated with TNBC ( 114 ).…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies had highlighted an anti-tumorigenic potential of hydroxytyrosol due to its capacity to protect against oxidative DNA damage in non-malignant MCF10A breast cells ( 113 ). More recently, hydroxytyrosol was shown to have inhibitory effects on breast cancer stem cell (BCSC) self-renewal in a comprehensive investigation using multiple TNBC cell lines ( 57 ). Tumor enrichment of BCSC has been suggested to play a role in the aggressiveness and poor prognosis associated with TNBC ( 114 ).…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 99%
“…Tumor enrichment of BCSC has been suggested to play a role in the aggressiveness and poor prognosis associated with TNBC ( 114 ). Hydroxytyrosol at a range of concentrations (0.5–100 μM) suppressed mammosphere-forming efficiency, a marker of BCSC self-renewal, of the TNBC cell lines SUM159PT, BT549, MDA-MB-231, and Hs578T ( 57 ). In fact, the 0.5 μM dose was sufficient to suppress mammosphere formation of SUM159PT cells by 40% and the three other TNBC cell lines (BT549, MDA-MB-231, and Hs578T) by 50% after 72 h in culture.…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra virgin olive oil (EVOO), the major source of fatty acids in the traditional Mediterranean diet, is rich in phenolic compounds, such as secoiridoid derivatives of 2‐(3,4‐dihydroxyphenyl)ethanol (hydroxytyrosol, HTy) and hydroxytyrosyl acetate (HTy‐Ac), which have a wide range of anti‐inflammatory, anti‐oxidant, and chemopreventive function in vitro . These beneficial properties were confirmed in vivo in animal models of autoimmunity …”
Section: Introductionmentioning
confidence: 97%
“…The main phenolic alcohol is hydroxytyrosol (HT). Several studies have demonstrated the beneficial properties of this compound in a number of models and cancer linked events 19 , particularly in breast cancer [20][21][22] . In fact, we have recently described that hypoxia modulates the antioxidant effect of HT in MCF-7 breast cancer cells 23 .…”
mentioning
confidence: 99%